Forming Religious Character Through Congregational Dhuha Prayers in Elementary School: Pembentukan Karakter Religi Melalui Shalat Dhuha Bersama di Sekolah Dasar - Anam, Moh. Misbakhul; Fahyuni, Eni Fariyatul (Indonesian Journal of Education Methods Development, 2025)
General Background: Religious character education at the elementary level plays a vital role in shaping students' moral and spiritual foundations. Specific Background: In the context of Islamic education, congregational Dhuha prayer has the potential to foster religious awareness and discipline among young learners. Knowledge Gap: However, empirical studies focusing on the implementation and impact of Dhuha prayer in elementary schools remain limited. Aims: This study aims to examine the effectiveness of congregational Dhuha prayers as a strategy to improve the religious character of elementary school students. Results: Using a qualitative descriptive approach through non-systematic observation and interviews, the findings reveal that students who regularly participate in Dhuha prayer demonstrate enhanced devotion to worship, increased spiritual awareness, improved discipline, greater responsibility, and growing confidence in religious practices. Novelty: This research highlights the practical application of routine Dhuha prayer as a character-building tool within Islamic education, particularly by empowering students to lead as prayer imams. Implications: The study underscores the importance of integrating structured religious practices into daily school routines and positions religious education teachers as pivotal facilitators in nurturing students’ religiosity and moral development from an early age. Highlights: Highlights Dhuha prayer as a strategy for building student religiosity. Shows improvement in discipline, responsibility, and worship habits. Emphasizes the teacher's role in shaping moral-spiritual character. Keywords: Religious Character, Dhuha Prayer, Islamic Education, Elementary Students, Spiritual Development